(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: In recent years, language education has shifted from traditional, teacher-centered methods to more dynamic, student-centered approaches. Among these, interactive group activities have gained significant attention for their ability to foster engagement, collaboration, and deeper language acquisition. The use of learning methods plays an important role and receives special attentions for a learner’s life. We live in digital era, where everyone wants something efficient, effective, dynamic, fast and interactive. Traditionally, most of the learners have been acquiring information and knowledge through less involvement of learners whereby learners only sit and listen to the unfaltering lectures. In addition, learners will copy down the endless indescribable notes that have been written on the whiteboard.